2009
DOI: 10.1038/modpathol.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

MGMT methylation is associated primarily with the germline C>T SNP (rs16906252) in colorectal cancer and normal colonic mucosa

Abstract: O6 -methylguanine DNA methyltransferase (MGMT) is a DNA repair protein that restores mutagenic O 6 -methylguanine to guanine. MGMT methylation is frequently observed in sporadic colorectal cancer and was recently correlated with the C4T allele at SNP rs16906252, within the transcriptional enhancer element of the promoter. MGMT methylation has also been associated with KRAS mutations, particularly G4A transitions. We studied 1123 colorectal carcinoma to define the molecular and clinicopathological profiles asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 42 publications
7
75
1
Order By: Relevance
“…This is in contrast to the c.-56C4T SNP (rs16906252) of the DNA repair gene MGMT, which correlates strongly with the presence of MGMT promoter methylation in both colorectal carcinoma and non-neoplastic tissues, illustrating that cis-acting elements can have an instrumental role in gene methylation. [43][44][45] The lack of any association between MLH1 methylation and the c.-93G4A genetic variant in our cohort is consistent with the finding, instead, of a strong correlation between methylation of MLH1 and neighbouring genes within the contiguous 3p22 chromosomal region, arguing for a fundamental epigenetic basis to MLH1 inactivation in sporadic microsatellite unstable tumours.…”
Section: Discussionsupporting
confidence: 90%
“…This is in contrast to the c.-56C4T SNP (rs16906252) of the DNA repair gene MGMT, which correlates strongly with the presence of MGMT promoter methylation in both colorectal carcinoma and non-neoplastic tissues, illustrating that cis-acting elements can have an instrumental role in gene methylation. [43][44][45] The lack of any association between MLH1 methylation and the c.-93G4A genetic variant in our cohort is consistent with the finding, instead, of a strong correlation between methylation of MLH1 and neighbouring genes within the contiguous 3p22 chromosomal region, arguing for a fundamental epigenetic basis to MLH1 inactivation in sporadic microsatellite unstable tumours.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, molecular data of these investigators indicated that when MGMT methylation occurred in heterozygous individuals, it occurred on the T allele. Another recent study has shown a similar association between the normal colonic mucosa and tumors of colorectal cancer patients and preferential methylation of the T allele in colorectal tumors (14).…”
mentioning
confidence: 71%
“…Promoter hypermethylation generally results in reduced gene and protein expression in somatic tissues. This inherited propensity toward epigenetic variation also referred to as "facilitated epigenetic variation" has been documented in a few specifi c cases in the scientifi c literature Chen et al 2007 ;Ogino et al 2007 ;Hawkins et al 2009 ;Raval et al 2007 ;Murrell et al 2004Murrell et al , 2011. For example, heritable cases of non-polyposis colorectal cancer caused by hypermethylation and gene silencing of MLH1 and MLH2 , have been associated with constitutional (germline) mutations and are also referred to as "epimutations" Chen et al 2007 ).…”
Section: Inherited Propensity Towards Epigenetic Inactivationmentioning
confidence: 94%
“…For example, heritable cases of non-polyposis colorectal cancer caused by hypermethylation and gene silencing of MLH1 and MLH2 , have been associated with constitutional (germline) mutations and are also referred to as "epimutations" Chen et al 2007 ). In colorectal cancer, an MGMT germline polymorphism (rs16906252 C>T) located within the transcriptional enhancer region was strongly associated with CpG island methylation and gene silencing in tumor tissue (Ogino et al 2007 ;Hawkins et al 2009 ). Epigenetic silencing and transcriptional suppression of the death associated protein kinase 1 gene ( DAPK1 ), a key underlying determinant in familial B cell chronic lymphatic leukemia, is associated with germline SNP (c.1-6531 A>G) located upstream from the DAPK1 promoter.…”
Section: Inherited Propensity Towards Epigenetic Inactivationmentioning
confidence: 99%